Wild fruits of Cameroon - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
A survey in Cameroon has examined all trees that produce fruit or seeds that are directly edible or can be used to prepare beverages or condiments. More than 300 species were identified for this inventory, including 200 forest species. Only some of...